Textural and mineralogical characteristics of SPM in coal mines - Jamal A.; Ratan S.; Dhar B.B. (My University, 2025)
The ultimate goal of air pollution assessment and control effort is to mitigate the effect of pollutants on environment. The effects may be on health, various other biological and systems, and physical quality of environnent. The severity of impact of airborned suspended particulate matter nay depends upon its physico-chemical properties. Opencast mining operation often generates high percentage of airborned Suspended Particulate Matter (SPM) which gets dissipated into the atmosphere around the mine and leads to serious disruption to the quality of the life. To this paper, a study of air quality monitoring in terms of SPM in an opencast coal mine has been presented. Among the various mining activities drilling, coal crushing and handling operations and movement of dumpers on the haul roads are the main sources of dust generation in an opencast coalmine. The concentration of SPM is variable throughout the year. It shows wide variation in summer and winter seasons in mining area. The mineral constituents present in the SPM also vary considerably.